2016
DOI: 10.1089/hum.2015.109
|View full text |Cite|
|
Sign up to set email alerts
|

Noninvasive Imaging Reveals Stable Transgene Expression in Mouse Airways After Delivery of a Nonintegrating Recombinant Adeno-Associated Viral Vector

Abstract: Gene therapy holds promise to cure a wide range of genetic and acquired diseases. Recent successes in recombinant adeno-associated viral vector (rAAV)-based gene therapy in the clinic for hereditary disorders such as Leber's congenital amaurosis and hemophilia B encouraged us to reexplore an rAAV approach for pulmonary gene transfer. Only limited clinical successes have been achieved for airway gene transfer so far, underscoring the need for further preclinical development of rAAV-based gene therapy for pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Furthermore, mouse models have been instrumental in addressing generic outcomes of gene therapy, ie, transduction efficiency, cell‐specific tropism, immune responses to vector and transgene, and longevity of gene expression (reviewed in Mingozzi and High). In non‐CF mouse airways, we have shown sustained reporter expression till 15 months after rAAV2/5 delivery, a substantial proportion of the lifespan of a laboratory mouse . Nevertheless, this question remains to be re‐investigated in an animal model spontaneously developing lung disease, such as the β‐ENaC overexpressing mouse or the CF rat, ferret, and pig .…”
Section: What Have Cf Mouse Models Taught Us About Gene Therapy?mentioning
confidence: 98%
“…Furthermore, mouse models have been instrumental in addressing generic outcomes of gene therapy, ie, transduction efficiency, cell‐specific tropism, immune responses to vector and transgene, and longevity of gene expression (reviewed in Mingozzi and High). In non‐CF mouse airways, we have shown sustained reporter expression till 15 months after rAAV2/5 delivery, a substantial proportion of the lifespan of a laboratory mouse . Nevertheless, this question remains to be re‐investigated in an animal model spontaneously developing lung disease, such as the β‐ENaC overexpressing mouse or the CF rat, ferret, and pig .…”
Section: What Have Cf Mouse Models Taught Us About Gene Therapy?mentioning
confidence: 98%
“…1 The research community has not yet reached a consensus for adeno-associated vectors (AAV), which is the current vector of choice for a range of eye disorders and haemophilia, for example. [5][6] However, in the context of lung gene transfer, we have not seen any convincing evidence that AAV can be re-administered without loss of efficacy and, therefore, currently question the further development of this vector for CF gene therapy. These data led the UK CF Gene Therapy Consortium (GTC; http://cfgenetherapy.org.uk/), which is currently the largest group pursuing translational CF gene therapy, to focus on non-viral gene transfer.…”
mentioning
confidence: 88%
“…Recently, a pseudotyped (hybrid) AAV gene vector, bearing AAV2 rep and AAV5 cap expression cassette (AAV2/5), achieved persistent gene transfer lasting up to 15 months in the airways and alveoli of mice following intratracheal administration (Figs. 1A, B) [105]. They also found that re-administration of AAV2/5 14 months after the initial administration did not significantly reduce the gene transfer efficacy, presumably due to the long dosing interval [105].…”
Section: Gene Delivery Platformsmentioning
confidence: 99%
“…They also found that re-administration of AAV2/5 14 months after the initial administration did not significantly reduce the gene transfer efficacy, presumably due to the long dosing interval [105]. As a result of this dosing interval, neutralizing antibody levels were reduced by more than 50% compared to peak levels after the first administration [105]. The process and rationale of pseudotyping viral gene vectors is discussed in detail in section 5.1.…”
Section: Gene Delivery Platformsmentioning
confidence: 99%
See 1 more Smart Citation